Analisis Kebijakan Pengentasan Kemiskinan di Era Pemerintahan Joko Widodo - Rizal, Dimas Ahmad; Purnairawan, Riski Eka (Journal of Social Movements, 2024)
Poverty is a fundamental issue faced by almost every country, especially developing ones. In Indonesia, the number of poor people in March 2022 reached 26.16 million or 9.54% of the total population. This article is the result of a literature review or library research. The research data were obtained from books, journals, research articles, documents, and other publications related to poverty alleviation policies. The research findings indicate that poverty alleviation policies during President Jokowi's administration are divided into three main programs: social assistance, subsidies, and the Village Fund. The social assistance program includes the Family Hope Program (PKH), Non-Cash Food Assistance Program (BPNT), Smart Indonesia Program, Student Aid Program (KIP Kuliah), and Receivers of Health Insurance Premium Assistance (PBI JKN). Although the social assistance program has had an impact on reducing the poverty rate, it is still not entirely effective due to targeting inaccuracies. Furthermore, the subsidy program includes both energy and non-energy subsidies. Energy subsidies are allocated for fuel, LPG, and electricity, while non-energy subsidies consist of fertilizer subsidies, Public Service Obligation (PSO) subsidies, credit program interest subsidies, and tax subsidies. The subsidy program is also considered less effective as it has not yet reached the intended targets. Lastly, the Village Fund, based on the literature, shows findings stating its effectiveness, but there are also research results indicating the opposite. This variation is influenced by different research areas, leading to diverse outcomes.